PENGARUH BEBAN KERJA, STRES KERJA, DAN WORK LIFE BALANCE TERHADAP TURNOVER INTENTION PENGAJAR DI LEMBAGA BIMBINGAN BELAJAR EXCELLENT COURSE DI KUDUS - Adinda, Adinda Adnadila Sani; Subarjo (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this study was to analyze the effect of workload, work stress, and work-life balance on turnover intention at the Excellent Tutoring Institute. The population in this study was 30 respondents. The sampling technique used in this study was the saturated sample technique. Data collection methods were interviews and questionnaires. This study used the coefficient of determination test technique, t-test, and F-test. The results showed that workload had a significant effect on affective turnover intention, work stress had a significant effect on turnover intention, and work-life balance did not have a significant effect on turnover intention. Keywords: Workload, work stress, work life balance